ZooMs MALDI spectra analysis in bone collagen of animal bones from the Pleistocene hyena den in Perspektywiczna Cave, Poland - Magdalena Krajcarz; Hervé Bocherens; Samantha Presslee; Maciej T Krajcarz (PANGAEA, 2024)
Dataset is a collection of MALDI ToF spectra files in a text format. These are supportive files for the dataset https://doi.pangaea.de/10.1594/PANGAEA.971340. Each file is a MALDI ToF-generated result for one sample of bone collagen of Late Pleistocene mammals from the Pleistocene hyena den in Perspektywiczna Cave (Poland) (https://doi.org/10.1017/RDC.2023.89). The bones were collected from cave clastic deposits, dated to MIS 3 (middle Weichselian or Weichselian Interpleniglacial) period, during archaeological excavations in 2013–2019 and are stored at the Institute of Archaeology, Nicolaus Copernicus University in Toruń (Poland). Data was collected for paleoecological purposes, for assessing the prey-to-hyena collagen-to-collagen Δ13C and Δ15N trophic discrimination factor (TDF). Each file extquotesingles name relates to the sample ID presented in column 20 of the https://doi.pangaea.de/10.1594/PANGAEA.971340 dataset. ZooMS analysis was performed at BioArCh, University of York, in 2021. Each sample was analyzed on a Bruker MALDI ToF MS (matrix assisted laser desorption ionisation time of flight mass spectrometry). The spectra were analyzed using mMass, an open-source mass spectrometry tool (https://doi.org/10.1021/ac100818g).